A Systematic Review of the Literature on the Clinical Presentation, Pathology, and Pathogenesis of Neonatal Dubin-Johnson Syndrome - Imad Abdien El Hag; A. Malik Alsheikh; Alaa M Bokhari; Khalid A Alghamdi; Mohamed I El Hag (The Indonesian Society of Pediatric Gastroenterology, Hepatology, and Nutrition, 2026)
Background: Neonatal Dubin-Johnson syndrome (DJS) is an unusual presentation of a rare autosomal recessive disease that typically manifests in adolescents. Methods: A thorough literature review was conducted, examining clinical, radiologic, morphological, and genetic features, as well as diagnostic pathways and long-term outcomes in neonatal-onset disease. The review adhered to the 2020 PRISMA guidelines, with study quality evaluated using the JBI checklist and influence assessed through leave- one-out analysis. Result: 141 cases were identified, most presenting within the first week as neonatal cholestatic liver disease. Males are affected twice as often as females. The condition is characterized by hyperbilirubinemia, elevated ALP, GGT, and bile acid levels, with normal transaminases. Common signs include hepatomegaly and acholic stools. Liver scintigraphy typically shows a bimodal pattern with excellent uptake but absent or delayed intestinal excretion, which may mimic biliary atresia (BA). Unlike BA, cholangiography appears normal. Liver biopsy reveals intrahepatic cholestasis (62%), paucity of interlobular bile ducts (22%), hepatopathy (33%), and steatosis (26%); the characteristic dark brown pigment is absent in 80% of cases. Fifty-five ABCC2 variants are associated with neonatal DJS. Additional risk factors include male sex, biliary immaturity, hepatitis, steatosis, bile acid retention, and maternally induced drug cholestasis. Urinary coproporphyrin I excretion, cholangiography, and genetic analysis are highly sensitive and specific diagnostic tools. Neonatal onset does not alter the disease's benign long-term course. Conclusion: Neonatal DJS should be considered in the differential diagnosis of neonatal cholestatic disease. Low transaminase levels and abnormal scintigraphy should prompt suspicion, with confirmation via cholangiography, coproporphyrin analysis, or genetic testing.